Gabor Systems about any Symmetric Points in Two Dimensions - Xincheng Zhang; Chenping zhao (Institute of Advanced Engineering and Science, 2014)
Gabor system plays an important role in signal processing, image processing and other applications because of their redundancy properties. In this paper, symmetric or antisymmetric Gabor frames in two dimensions about any symmetric points are constructed from Gabor frames given. In special, symmetric or antisymmetric Parseval Gabor frames with better properties are obtained. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3370